Effectiveness and cost‐effectiveness of the Transmural Trauma Care Model investigated in a multicenter trial with a controlled before‐and‐after design: A study protocol. (21st January 2021) - Ratter, Julia; Wiertsema, Suzanne; van Dongen, Johanna M.; Geleijn, Edwin; Ostelo, Raymond W. J. G.; de Groot, Vincent; Bloemers, Frank W.
Abstract: Objective: The rehabilitation of trauma patients in primary care is challenging, and there are no guidelines for optimal treatment. Also, the organization of care is not well‐structured. The Transmural Trauma Care Model (TTCM) has been developed in the Netherlands, aiming to improve patient outcomes by optimizing the organization and the quality of the rehabilitation process in primary care. A recent feasibility study showed that implementation of the TTCM at a Dutch Level 1 trauma center was feasible, patient outcomes were improved, and costs were reduced. This study aims to assess the effectiveness and cost‐effectiveness of the TTCM compared to the usual care in a multicenter trial. Methods: A multicenter trial with a controlled before‐and‐after design will be performed at 10 hospitals in the Netherlands. First, participating hospitals will include 322 patients in the control group, receiving usual care as provided in these specific hospitals. Subsequently, the TTCM will be implemented in all participating hospitals, and hospitals will include an additional 322 patients in the intervention group. The TTCM consists of a multidisciplinary team at the outpatient clinic (trauma surgeon and hospital‐based physical therapist), an educated and trained network of primary care trauma physical therapists, and structural communication between them. Co‐primary outcomes will investigate generic and disease‐specific, health‐related quality of life. Secondary outcomes will include pain, patient satisfaction, perceived recovery, and patient‐reported physical functioning. For the economic evaluation, societal and healthcare costs will be measured. Measurements will take place at baseline and after 6 weeks, 3, 6, and 9 months. Analyses will be based on the intention‐to‐treat principle. Missing data will be handled using longitudinal data analyses in the effect analyses and by multivariate imputation in the economic evaluation. Conclusion: This trial with a controlled before‐and‐after design will give insight into the effectiveness and cost‐effectiveness of the TTCM in a multicenter trial.